Pengaruh Pengalaman Kerja, Gaya Kepemimpinan dan Insentif Terhadap Kinerja Karyawan BRI KCP Wirobrajan Yogyakarta - Shinta Ardynita Putra; Sudarmadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Research to ascertain how incentives, leadership style, and work experience affect BRI KCP Wirobrajan Yogyakarta employees' performance. The study is quantitative and use the survey approach. Seventy-two workers of BRI KCP Wirobrajan Yogyakarta served as the samples. Questionnair, interview, with observation are the methods used to find data research. Various techniques for analyzing this research data include descriptive statistical analysis, respondent characteristic analysis, data quality tests consisting of validity and reliability tests, classical assumption tests, namely autocorrelation tests, heteroscedasticity tests, multicollinearity tests, and normality tests, and model tests are used, namely the R2 test, F test or simultaneous analysis, and hypothesis testing through the t test for partial tests and multiple linear regression analysis. The study concludes that incentives, leadership style, and work experience all significantly and favorably affect BRI KCP Wirobrajan Yogyakarta employees' performance. Employee performance may be explained by work experience, leadership style, and incentives in 68.5% of cases.